SUPERVISI LAYANAN PENDIDIKAN DAN TERAPI INDIVIDUAL PADA ANAK ADHD USIA DINI DI YAUMI FATIMAH SPECIAL SCHOOL - Suryadin, Adin; Wahyuningsih, Endah Tri (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) face complex challenges in concentration and behavioral control, requiring intensive and structured educational interventions outside the regular system. This study aims to analyze the effectiveness of integrated educational service supervision in special classes at Yaumi Fatimah Special School and its impact on the developmental progress of children with ADHD in early childhood. The research method used a descriptive qualitative approach, with data collection techniques through participatory observation, in-depth interviews, and documentation studies over a full semester. The educational service process implemented integrated an Islamic values-based kindergarten curriculum with individual therapeutic interventions that included sensory integration, occupational therapy, speech therapy, and behavioral therapy tailored to each child's specific needs. The research findings indicate that the strategy of integrating character education and intensive therapy is able to stimulate positive behavioral changes holistically. Based on the results of the end-of-semester evaluation, significant improvements were recorded in aspects of eye contact, concentration, and social interaction, as evidenced by quantitative data in the form of an average increase in ability development scores ranging from 20 to 30 digits. The main conclusion of this study confirms that an integrated educational program and personalized therapy are highly effective in optimizing the potential of children with ADHD, with some students even demonstrating readiness for transition to regular elementary school. ABSTRAK Anak dengan Attention Deficit Hyperactivity Disorder (ADHD) menghadapi hambatan kompleks dalam konsentrasi dan pengendalian perilaku yang memerlukan penanganan pendidikan intensif dan terstruktur di luar sistem reguler. Penelitian ini bertujuan untuk menganalisis efektivitas supervisi layanan pendidikan terpadu di kelas khusus Yaumi Fatimah Special School serta dampaknya terhadap progres perkembangan anak ADHD usia dini. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi selama satu semester penuh. Proses layanan pendidikan yang diterapkan mengintegrasikan kurikulum Taman Kanak-kanak berbasis nilai Islam dengan intervensi terapi individual yang mencakup terapi sensori integrasi, okupasi, wicara, dan perilaku sesuai kebutuhan spesifik setiap anak. Temuan penelitian menunjukkan bahwa strategi pemaduan pendidikan karakter dan terapi intensif mampu menstimulasi perubahan perilaku positif secara holistik. Berdasarkan hasil evaluasi akhir semester, tercatat perkembangan signifikan pada aspek kontak mata, konsentrasi, dan interaksi sosial, yang dibuktikan dengan data kuantitatif berupa rata-rata kenaikan skor perkembangan kemampuan berkisar antara 20 hingga 30 digit. Simpulan utama penelitian ini menegaskan bahwa program pendidikan terpadu dan personalisasi terapi sangat efektif dalam mengoptimalkan potensi anak ADHD, di mana beberapa siswa bahkan menunjukkan kesiapan transisi menuju jenjang pendidikan dasar reguler.